High Energy Radical Chemistry Formation of HCN-rich Atmospheres on early Earth - Martin Ferus (Nature Portfolio, 2017)
Abstract Recent results in prebiotic chemistry implicate hydrogen cyanide (HCN) as the source of carbon and nitrogen for the synthesis of nucleotide, amino acid and lipid building blocks. HCN can be produced during impact events by reprocessing of carbonaceous and nitrogenous materials from both the impactor and the atmosphere; it can also be produced from these materials by electrical discharge. Here we investigate the effect of high energy events on a range of starting mixtures representative of various atmosphere-impactor volatile combinations. Using continuously scanning time–resolved spectrometry, we have detected ·CN radical and excited CO as the initially most abundant products. Cyano radicals and excited carbon monoxide molecules in particular are reactive, energy-rich species, but are resilient owing to favourable Franck–Condon factors. The subsequent reactions of these first formed excited species lead to the production of ground-state prebiotic building blocks, principally HCN.